Call for papers: NJL Special Issue on Prosody in the Nordic Languages. Issue 1 (6th May 2014) - Horne, Merle; Roll, Mikael
<x content-type="archive" xml:space="preserve">Abstract</x> The second issue of Volume 38 (autumn 2015) of the Nordic Journal of Linguistics will be a special issue devoted to prosody in the Nordic languages. The special issue will be edited by Merle Horne and Mikael Roll.